Instructional communication in inclusive deaf education: a global and Asian bibliometric review - Siti Farisah Yahya; Syar Meeze Mohd Rashid; Khairul Farhah Khairuddin (Institute of Advanced Engineering and Science, 2026)
Instructional communication supports equitable access, participation, and learning in inclusive deaf education. However, evidence on how this field has evolved globally, particularly in Asian contexts, remains fragmented. This bibliometric review analyses 423 Scopus-indexed publications (2015–2025) using performance indicators and science-mapping techniques to examine publication trends, collaboration networks, thematic structures, and intellectual development. The findings indicate sustained growth after 2018, driven by global inclusion agendas and the expansion of digital learning environments. While research increasingly emphasizes multimodal pedagogy, inclusive practices, and technology-enhanced communication, collaboration networks remain dominated by Western institutions. Asian contributions, although growing, are more visible in emerging technology-oriented domains than in foundational theoretical cores. The study identifies a shift from clinically oriented approaches toward integrated, multimodal, and digitally mediated instructional communication frameworks. It further reconceptualizes instructional communication as an evaluative indicator of inclusive teaching quality, reflecting access, interaction, and pedagogical responsiveness. These findings highlight the need for stronger regional research capacity, context-sensitive theoretical development, and more inclusive global knowledge structures. The study has implications for policy development, teacher training, and curriculum design in multilingual and technologically diverse educational systems, particularly across Asia.